2013
DOI: 10.1039/c3cp50980j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical characterisation of triphenylamine-based hole extractor materials for CdSe quantum dots

Abstract: We report the synthesis and optical characterisation of different triphenylamine-based hole capture materials able to anchor to CdSe quantum dots (QDs). Cyclic voltammetry studies indicate that these materials exhibit reversible electrochemical behaviour. Photoluminescence and transient absorption spectroscopy techniques are used to study interfacial charge transfer properties of the triphenylamine functionalized CdSe QDs. Specifically, we show that the functionalized QDs based on the most easily oxidised trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Over the past two decades, there are many demonstrations of ultrafast (<1 ns) charge transfer from photoexcited QDs or semiconductor quantum rods (QRs) to organic molecules or polymers, Table . , ,,, A recent article also reviews this work in more detail …”
Section: Role Of Molecules In Energy and Charge Transfer Involving Co...mentioning
confidence: 99%
“…Over the past two decades, there are many demonstrations of ultrafast (<1 ns) charge transfer from photoexcited QDs or semiconductor quantum rods (QRs) to organic molecules or polymers, Table . , ,,, A recent article also reviews this work in more detail …”
Section: Role Of Molecules In Energy and Charge Transfer Involving Co...mentioning
confidence: 99%
“…One can see the semi-infinite linear diffusion limited voltammogram having the positive and negative current peaks, indicating the simple redox of TPTA. 52,56 TPTA(IL) " TPTA + (IL) + e À…”
Section: Soejima Et Al Utilized Linear Aggregates Of Tetrabutylammoni...mentioning
confidence: 99%
“…It is stoichiometric and composed of 82 TiO 2 units; denoted as (TiO 2 ) 82 or TiO 2 (101) hereafter. The TiO 2 slab exposing the (001) facet is non-stoichiometric and we have added 24 OH À groups to compensate for the Ti excess of the pristine slab; denoted as (Ti 143 O 274 )(OH) 24 or TiO 2 (001) hereafter. We opted for cluster models for the TiO 2 surfaces because they allow hybrid DFT calculations and inclusion of solvent effects, mandatory for a proper description of the band edge states of the oxide.…”
Section: Qd Modelsmentioning
confidence: 99%
“…16 Despite these promising results, PbS QDSCs, however, have performed quite disappointingly if we compare them to their dye sensitized counterparts holding a record PCE of 12.3% 17 and the more recent perovskite solar cells with a PCE of 19.3%. 18 The reasons why QDSCs still present low efficiencies have been thoroughly investigated and following facts could be inferred: (a) QDs display localized surface states (trap states) that block the flow of charge carriers into the circuit; 19,20 (b) the interfacial electron injection from the QD to the metal oxide competes with several deleterious fast recombination pathways; [21][22][23][24] (c) the polysulphide electrolyte couple employed in sensitized QDSCs present a high redox potential that lower the opencircuit voltage and therefore the overall PCE. 25 In a recent work by Etgar et al on PbS-TiO 2 heterojunction solar cells, the surface of the oxide has been shown to play a crucial role on the performance of the device.…”
Section: Introductionmentioning
confidence: 99%